Evaluation of the Effects of Iron Oxide Nanoparticles on Expression of TEM Type Beta-Lactamase Genes in Pseudomonas Aeruginosa - Mina Lotfpour; Kumarss Amini (Journal of Sciences, Islamic Republic of Iran)
Pseudomonas aeruginosa is a common cause of surgical-site infections and healthcare-associated infections in the bloodstream, and urinary tract. Iron oxide nanoparticles (IONPs) have shown, to possess antibacterial features. The nanoparticles' status as emerging therapeutic elements has motivated investigators to assess the effects of iron nanoparticles on the expression of TEM type beta-lactamase genes in P. aeruginosa. In this descriptive-analytic study, 60 clinical isolates of P. aeruginosa were isolated from burn wounds and respiratory excretions of Pasargad Research Laboratory of Tehran, Iran. All isolates were characterized using differential biochemical tests and confirmed samples as P. aeruginosa. Their genomic DNA was extracted and PCR reaction was performed to screen TEM-gene carrying isolates. Then MIC of IONPs against these strains was determined and finally, Real-time PCR performed to the determination of the expression of the TEM gene. Results showed that 8 isolates (13/33%) had the TEM beta-lactamase gene. The MIC and MBC of IONPs against P. aeruginosa strains were observed at 256 µg/mL or 125 µg/mL, while the MBC was determined at 500 µg/mL. In addition, statistical analysis of Real-time PCR data showed that there is a statistically significant difference between gene expression levels of IONPs treated isolates and non-treated ones. The results showed that TEM gene expression levels in two isolates treated with IONPs were 78% and 75% lower than untreated bacteria (P<0.001; r= 0.958). Our findings confirmed that IONPs are potential antibacterial agents and can be considered as promising treatments for recalcitrant P. aeruginosa infections.